Pengembangan Potensi Wisata Berbasis Partisipasi Masyarakat Lokal Di Desa Jelantik Kecamatan Jonggat Lombok Tengah - Muh Bagus Budianto; Bambang Harianto; Anid Supriadi; Agustono Setiawan; Eko Pradjoko (Universitas Mataram, 2022)
Jelantik Village is one of the 13 (thirteen) villages in Jonggat District. Jelantik Village has various undeveloped tourism potentials including beautiful river channels, geotourism tourism potential, shadow puppet art cultural tourism, bicycle tracks with beautiful views of rice fields, and has the Jelantik Dam (Telaga Ijo) which has stunning views. Among the tourism potentials in Jelantik Village, the Jelantik Dam has the most potential to attract tourists. Some of the advantages of the Jelantik Dam include beautiful scenery, fresh air, easy access from the main Praya-Mataram road and culinary delights. The purpose of this activity is the arrangement of the Telaga Ijo area. The methods used in this activity are site surveys and questionnaires. A site survey is conducted to determine the physical condition of the dam and the people around it. Meanwhile, a questionnaire was given to visitors to get an overview of tourists' wishes. The survey results show that the Jelantik Dam is flanked by rice fields, has a beautiful view of the trees surrounding the lake. Communities around the dam support the development of the dam. Based on the questionnaire, tourists want boat tours, bicycle paths around the lake, spots for selfies, parking lots, additional berugak, trees for shelter, additional sales stalls, sports facilities and facilities for horse riding around the lake. The conclusion of this area arrangement activity is as a reference in the development and construction of facilities and infrastructure that support tourism activities at the Jelantik Dam (Telaga Ijo).